2020
DOI: 10.5430/jnep.v10n8p19
|View full text |Cite
|
Sign up to set email alerts
|

A lack of allocated research time challenges the extent of the implementation of evidence-based practice - A three-year retrospective follow-up cohort study of Master of Science in Nursing graduates

Abstract: Objective: To describe and compare the development of Master of Science in Nursing graduates’ research utilization and improvement of knowledge, one to three years after graduation, and to describe their beliefs, abilities and implementation regarding evidence-based practice in the workplace.Methods: Sixty-five Master of Science in Nursing (MSN) graduates, associated with an academic cohort, were invited to participate in a three-year retrospective follow-up study. Forty-five MSN graduates replied, providing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Other studies have also identified researchers' balance between research and clinical work as problematic (Berthelsen, Martinsen, & Vamosi, 2020; Berthelsen, Vamosi, & Martinsen, 2020; Clark et al, 2015; Loke et al, 2014). A cohort study of Master of Science in Nursing graduates showed that their dual positions involving both research and patient care often restrained them because their research‐related tasks were often withdrawn if they were needed in patient care owing to the absence of their colleagues (Berthelsen, 2020). The cohort also showed a large decrease in the master graduates' time for research: 74.3% spent less than 5 h/week on research from 1 to 3 years after graduation (Berthelsen, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also identified researchers' balance between research and clinical work as problematic (Berthelsen, Martinsen, & Vamosi, 2020; Berthelsen, Vamosi, & Martinsen, 2020; Clark et al, 2015; Loke et al, 2014). A cohort study of Master of Science in Nursing graduates showed that their dual positions involving both research and patient care often restrained them because their research‐related tasks were often withdrawn if they were needed in patient care owing to the absence of their colleagues (Berthelsen, 2020). The cohort also showed a large decrease in the master graduates' time for research: 74.3% spent less than 5 h/week on research from 1 to 3 years after graduation (Berthelsen, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study of Master of Science in Nursing graduates showed that their dual positions involving both research and patient care often restrained them because their research‐related tasks were often withdrawn if they were needed in patient care owing to the absence of their colleagues (Berthelsen, 2020). The cohort also showed a large decrease in the master graduates' time for research: 74.3% spent less than 5 h/week on research from 1 to 3 years after graduation (Berthelsen, 2020). This could indicate that the usual barrier of lack of time for research (Van Oostveen et al, 2017) and the prioritizing of urgent daily demands (Hølge‐Hazelton et al, 2016) is even more a problem during the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%